The future of U.S. Empire in the Americas
1 online resource
Keywords: "With the rise of President Trump, many are coming to question where the United States (U.S.) is headed and, whether we might witness an imperial decline under Trump. Social scientists largely recognize the contemporary hegemonic position of the U.S. at the global level, but questions persist concerning the future of U.S. Empire. With the Trump Administration at the helm, these questions are all the more salient. Drawing on the expertise of a panel of contributors and guided by Michael Mann's model of power, this book critically interrogates the future of U.S. global power and provides insights on what we might expect from the U.S. Empire under Trump. Recognizing that U.S. imperial power involves an array of sources of power (ideological, economic, military, and political), the contributors analyze the Trump Administration's approach towards nine countries in the Western Hemisphere, and five sets of global policies, including inter-American relations, drugs, trade, the environment, and immigration. Each case presents a historical look at the trajectory of relations as they have developed under Trump and what we might expect in the future from the administration. The Future of U.S. Empire in the Americas will be of great interest to students and scholars of U.S. foreign policy, Foreign Policy Analysis, political sociology, and American politics"--